2022
DOI: 10.1186/s13148-022-01284-w
|View full text |Cite
|
Sign up to set email alerts
|

The mediating effect of DNA methylation in the association between maternal sleep during pregnancy and offspring adiposity status: a prospective cohort study

Abstract: Background Childhood overweight/obesity is a global public health concern. It is important to identify its early-life risk factors. Maternal poor sleep is common in late pregnancy, and previous studies indicated that poor sleep may influence the offspring’s adiposity status. However, very few studies in humans investigated the effect of the different sleep parameters (sleep quantity, quality, and timing) on the offspring’s adiposity indicators, and long-term studies are even more scarce. In add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 67 publications
(70 reference statements)
0
5
0
1
Order By: Relevance
“…Foi realizado um estudo de coorte, entre os anos de 2012 a 2016 com 2.211 mulheres que tiveram uma única gestação, e as medidas de IMC da sua respectiva prole aos 02 anos de idade. Essa pesquisa demonstrou que o sono deficiente da mãe no final da gestação, interfere na metilação do DNA do cordão umbilical, e consequentemente isso pode estar associado a um aumento no estado de adiposidade fetal (Meng et al, 2022).…”
Section: Yang Et Al (2022)unclassified
“…Foi realizado um estudo de coorte, entre os anos de 2012 a 2016 com 2.211 mulheres que tiveram uma única gestação, e as medidas de IMC da sua respectiva prole aos 02 anos de idade. Essa pesquisa demonstrou que o sono deficiente da mãe no final da gestação, interfere na metilação do DNA do cordão umbilical, e consequentemente isso pode estar associado a um aumento no estado de adiposidade fetal (Meng et al, 2022).…”
Section: Yang Et Al (2022)unclassified
“…Building upon prior research, Meng et al (2022) embarked to elucidate the association between three distinct maternal sleep dimensions during late pregnancy and offspring adiposity markers [ 106 ]. Their investigation further aimed to explore the potential mediating effect of cord blood DNA methylation [ 98 ].…”
Section: Transgenerational Epigenetic Changes and Changes In Sleep Pa...mentioning
confidence: 99%
“…Their investigation further aimed to explore the potential mediating effect of cord blood DNA methylation [ 98 ]. Employing an epigenome-wide association study design, they sought to identify maternal sleep-related CpG sites potentially linked to maternal sleep patterns [ 106 ]. Notably, the study revealed a significant association between later maternal sleep timing in late pregnancy and increased childhood adiposity in offspring, with cord blood DNA methylation emerging as a putative mediator in this relationship [ 106 ].…”
Section: Transgenerational Epigenetic Changes and Changes In Sleep Pa...mentioning
confidence: 99%
See 2 more Smart Citations